Comparative Analysis of CBRM Cases in Kenya, Ethiopia and Tunisia - Ng'ang'a, I.N.; Robinson, Lance W.; Eba, B.; Flintan, Fiona E.; Ontiri, E.M.; Sghaier, M.; Abdu, N.H.; Moiko, Stephen S. (International Livestock Research Institute, 2021)
In various countries, development and conservation organizations and national policymakers have been experimenting with ways of applying the community-based natural resource management approach to the unique social and biophysical characteristics of pastoralist rangeland settings, with mixed results. We carried out comparative case study research on community-based rangeland management (CBRM) in a variety of settings in Ethiopia, Kenya and Tunisia with the objective of identifying what kinds of strategies and methods work in which social and ecological contexts. We used an 'options by context' approach guided by a research protocol that includes key variables and descriptors for characterizing the implementing organization's approach to CBRM and important contextual factors that may vary from place to place and affect the implementation and success of the approach. The commonalities among our cases include: i) community governance and management structures for rangeland management; ii) the geographic rangeland unit which those structures are managing, and iii) a development agent that is supporting the community. We found that differences among the cases in the challenges faced and their degree of success depended at least as much on certain aspects of social and biophysical context as it did on the exact nature of the approach being implemented by the development agent. For example, the extent to which there are effective natural or social borders that provide the rangeland community with some degree of separation from neighbours is crucial; without such landscape features, the design principle of clearly defined rights to a clearly defined piece of land belonging to a clearly defined community is difficult to implement in any straightforward way. In some pastoral rangeland contexts, conventional community-based approaches need substantial modification to be effective in contexts with the highest levels of spatio-temporal variability, mobility and openness of the landscape.